Enhancing tensile and fatigue properties of high-speed-extruded Mg–5Bi–3Al alloy using non-homogenized extrusion billet - Sumi Jo; Jung Eun Kim; Ye Jin Kim; Sang-Cheol Jin; Sung Hyuk Park (Journal of Materials Research and Technology)
This study aims to improve the tensile and high-cycle fatigue properties of a high-speed-extruded BA53 (Mg–5Bi–3Al, wt.%) alloy using a non-homogenized extrusion billet. Homogenization treatment of the BA53 billet leads to a significant reduction in the area fraction of Mg3Bi2 particles from 12.9% to 2.5% and an increase in the average grain size from 142 to 189 μm. The BA53 material produced via the high-speed extrusion of the cast billet (Cast-E) and that produced via the high-speed extrusion of the homogenized billet (Homo-E) both exhibit a fully recrystallized microstructure. However, Cast-E has a finer grain size and many more Mg3Bi2 particles than Homo-E. In addition, the tensile yield strength and elongation of Cast-E are 211 MPa and 9.4%, respectively, higher than those of Homo-E (198 MPa and 7.9%). This higher strength is attributed to the strengthening effects of the higher number of Mg3Bi2 particles, the finer grain size, and the higher internal strain energy. The fatigue limit for Cast-E is 100 MPa, which is 25% higher than that of Homo-E (80 MPa). This occurs because the numerous fine Mg3Bi2 particles in Cast-E inhibit the formation of persistent slip bands on the specimen surface and impede crack propagation. This study proposes a new manufacturing process that does not require billet homogenization, thus simultaneously improving the productivity of the extrusion process and the tensile and fatigue properties of the resulting BA53 alloy.